Symbolic Interactionism in Poland. Inspirations and Development - Konecki, Krzysztof T.; Kacperczyk, Anna (Qualitative Sociology Review, 2020)
In the paper, we present the development of symbolic interactionism (SI) in Poland by tracing and discussing its beginnings, as well as the influence the Chicago School had on the reception of SI in Polish sociology. Furthermore, we differentiate between two trends in the development of SI in Poland. One is connected with the early theoretical elaborations of the SI orientation and translations of classical books representing this perspective; another is linked with empirical work underpinned by SI concepts and the grounded theory approach in empirical research and data analysis. Stressing the importance of translations of classical texts of SI in its reception in Poland, we emphasize the role of field research and applications of SI concepts in sociological investigations that we shortly characterize.